Perspective of the Gonting Julu Village Community, Huristak District, Padang Lawas Regency Regarding Delays in the Distribution of Inheritance - Novi Arbaini Daulay; Amal Hayati (Warmadewa Press, 2024)
This research aims to understand the perspective of the community in Gonting Julu Village, Huristak District, Padang Lawas Regency, regarding the delay in the distribution of inheritance, which often is not promptly executed. The delay in inheritance distribution has become a common practice. The problems addressed in this study include understanding the legal aspects of delaying inheritance distribution for heirs according to Islamic law and exploring the perspectives of the Gonting Julu village community that contribute to the factors causing the delay in inheritance distribution in Gonting Julu Village. This research employs a qualitative method with a case study approach. It examines the applicable legal provisions and what occurs in reality within the community. The primary data sources for this research are community leaders, local elders, and the residents of Gonting Julu Village. Secondary data sources include documents, books, articles, internet searches, and more. Inheritance is essentially a trust to the heirs; the inheritance is a fiduciary fund that must be passed on to the rightful heirs. However, many residents of Gonting Julu Village often do not promptly distribute inheritance, making the delay a habitual practice. The findings of this study reveal that the community has not yet promptly distributed inheritance according to Islamic law, and it remains a deeply ingrained habit. The factors contributing to the delay in inheritance distribution include respecting the feelings of surviving parents and managing the inheritance.